Pengaruh Penerapan Sistem Informasi Manajemen Nikah (SIMKAH) Terhadap Kinerja Pegawai - Hana Putri; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled “The Effect of Implementing the Marriage Management Information System (SIMKAH) on Employee Performance at the District Religious Affairs Office. Sematang Form”. SIMKAH is a policy program issued by the government to be implemented at the District KUA which aims to facilitate the presentation of marriage data at the KUA. The aim of this research is to determine the effect of implementing SIMKAH on employee performance at KUA Kec. Semang Form. This type of research uses a quantitative approach. The source data used is primary and secondary data. The data collection techniques used in this research are questionnaires and documentation. Sampling was carried out using all 31 KUA employees. The analysis technique used in this research is quantitative analysis with validity tests, reliability tests, basic assumption tests (data normality test, linearity test, homogeneity test). The results of this research show that there is an influence of implementing SIMKAH on employee performance, this can be seen from the results of management data using SPSS version 26 which obtained a calculated t value <t table (0.054<1.812) and a significant value of 0.957>0.05. This is also the coefficient of determination or R of 0.128 which shows that 12.8% has no influence while the remaining 87.2% is influenced by other factors not studied.